The future of foreign direct investment and the multinational enterprise - Ramamurti, Ravi; Hashai, Niron (Research in global strategic management ;, 2011)
The policy and technological context within which FDI takes place has changed dramatically in the last two decades. Countries around the world have become more open to FDI, and revolutions in information and communications technology have lowered the costs of internationalization. As a result, global FDI flows have swelled, but, just as important, the forms that it takes have become more complex. For instance, emerging markets are now spawning MNEs of their own, governments and private equity firms are engaging in FDI, global sourcing is becoming central to the strategies of many firms, and offshoring encompasses many services, including high-end R & D work. In turn, these developments are exposing the limitations of the fields theoretical foundations. This Festschrift in honour of Professor Yair Aharoni, a pioneer in the field of international business, looks at several of these new trends in FDI, what they will mean for firms and governments, and the opportunities created by these developments to enrich or extend extant theory. Contributors to the volume include the worlds leading international business scholars.